ANALISIS K3 PADA BAGIAN PRODUKSI MENGGUNAKAN METODE HAZARD AND OPERABILITY (HAZOP) - Nurlailwinaya, Nugraha; Andung Jati Nugroho (Kampus Akademik Publiser, 2024)
PT. Albasi Karanglayung Indonesia is one of the companies engaged in the wood industry to produce barecore product. Based on the collection of work accident data over a period of one year, namely in 2023, there will be eleven accidents in five accident locations, namely jumping machines, multirif machines, press crosscut machines, pull crosscut machines, press machines, and warehouses, this occurs due to several factors, namely human and machine factors. The design of recommendations or proposed improvements is carried out based on hazards (potential hazards) that occur. The Hazard And Operability method aims to overcome these problems, with the expectation of reducing the risk of work accidents in the production area of PT. Albasi Karanglayung Indonesia. Potential sources of hazard from the six potential hazard locations two of them have a high risk level, namely a press crosscut machine and a pull crosscut machine, while the rest have a medium risk level, namely jumping machines, multirif machines, press machines, and warehouses. After the analysis of the results of data processing, recommendations were found to minimize and suppress the occurrence of work accidents, namely further improving the use of PPE for workers and providing K3 training so that workers can understand the importance of safety for themselves and others around them and the holding of sanctions for those who violate the provisions.